ANALYSIS OF YOUNG MALE AND FEMALE PREFERENCES IN CHOOSING INTERNATIONAL FASHION BRAND IN MANADO - Rori, Riebka Praisylia; Lambey, Linda .; Rumokoy, Farlane Stevie (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Brand is the personality that indetifies a product, service, or company (name, term, sign, symbol, or design, or combination of them). This research aims to determine if there is any significant difference in young male and female preference in choosing International fashion Brand in Manado. The type of this research is a quantitative decriptive research. Independent Sample T-Test was used in this research. The samples are divided into 50 young males and 50 young females. The sample was taken by purposive sampling. The result shows; (1) There are no siginificant differences in term of style, popularity of brand and land of origin. (2) There are significant differences in ters of promotion and quality of product. Based on the result, international brand should improve their performance in term of develop new product.Keywords: Young Male and Female, Independent sample t-test, International fashion brand